2016
DOI: 10.18632/oncotarget.12722
|View full text |Cite
|
Sign up to set email alerts
|

Effect of marital status on the survival of patients with hepatocellular carcinoma treated with surgical resection: an analysis of 13,408 patients in the surveillance, epidemiology, and end results (SEER) database

Abstract: Marital status has been reported as an independent prognostic factor for survival in various cancers, but it has been rarely studied in hepatocellular carcinoma (HCC) treated by surgical resection. We retrospectively investigated Surveillance, Epidemiology, and End Results (SEER) population-based data and identified 13,408 cases of HCC with surgical treatment between 1998 and 2013. The patients were categorized according to marital status, as “married,” “never married,” “widowed,” or “divorced/separated.” The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 30 publications
5
18
0
Order By: Relevance
“…Though most of the findings of this study are consistent with the findings of previous observational studies conducted on other types of cancer [ 8 , 12 , 17 , 18 ], that unmarried patients had survival disadvantage compared with married patients, the significance of this study is that we analyzed the effect of marital status on the OS and EOCSS according to different stages and repeated the analyses for patients who underwent surgery, which had never been investigated for ovarian cancer before.…”
Section: Discussionsupporting
confidence: 89%
“…Though most of the findings of this study are consistent with the findings of previous observational studies conducted on other types of cancer [ 8 , 12 , 17 , 18 ], that unmarried patients had survival disadvantage compared with married patients, the significance of this study is that we analyzed the effect of marital status on the OS and EOCSS according to different stages and repeated the analyses for patients who underwent surgery, which had never been investigated for ovarian cancer before.…”
Section: Discussionsupporting
confidence: 89%
“…In addition, it pointed out that the widowed patients always endured the highest risk of mortality for OS and TCSS. The meaning of this study lies in the important impact of marital status on survival of oral tongue squamous cell carcinoma, which is in consistency with previous researches of other cancers [ 17 20 ].…”
Section: Discussionsupporting
confidence: 87%
“…Previously published articles also indicated that marital status was considered as a prognostic factor of better survival in liver cancer. 19 , 20 Less well investigated, however, is the influence of race/ethnicity and gender in the association between being married and overall prognosis of HCC. Therefore, we performed a population-based study to fill the gap on racial and gender differences in marriage-associated survival benefits,…”
Section: Introductionmentioning
confidence: 99%